Availability evaluation of repairable system requiring two types of supporting device for operations - Fagge, Nura Jibrin; Yusuf, Ibrahim; Ali, U.A. (International Journal of Applied Mathematical Research, 2017)
With advancement of modern science and technology, complex systems connected to an external supporting device for their operations have been manufactured to meet the demand of industries, economic growth and populace in general. Companies and organizations heavily rely on these systems to conduct their business. This study presents the availability assessment of a single unit system connected to two types of an external supporting device for its operation. Each type of supporting device has two copies I and II. First order differential equations method is used to obtain the explicit expression for the steady-state availability. Based on assumed numerical values given to system parameters, graphical illustrations are given to highlight important results. Comparisons are performed to highlight the impact of unit failure and repair rates.